Gambaran Praktik Pengasuhan Anak Kembar di Kabupaten Gayo Lues - Wani, Surna; Magistarina, Elrisfa (AHKAM, 2024)
The purpose of this study is to know the image of the practice of child care in gayo lues district. This study uses qualitative methods with a descriptive approach. Number of participants in the study are three subjects. The data is analyzed using thematic analysis techniques. The findings suggest that there are 7 themes illustrating the practice of foster care in gayo lues district, of which 7 include the following sub themes. Parenting stress that covers the subtheme of financial demands, the lack of time for yourself. Support system that includes sub themes of extended family help, husband support, local government assistance. Coping strategies that include the subtheme manage time through other work, not managing emotions in a healthy way. Teaching that includes sub themes that enhance understanding, direction and example. The culture that includes the sub theme educating children firmly, the high tone of voice and educating children independently. The vaforitism consists of the sub theme divide and contrast.